Australian Transnational Higher Education: Rethinking the Value Proposition - Lim, Fion (International Higher Education, 2024)
<h3 id="australian-international-higher-education-is-facing-a-crisis-as-visa-approval-rates-plummeted-in-2024-affecting-institutions-and-potential-students-the-higher-education-sector-faces-the-gloomy-uncertainty-of-a-cap-to-be-introduced-on-international-student-enrollments-the-australian-government-has-urged-higher-education-institutions-to-set-up-more-offshore-delivery-however-the-business-as-usual-approach-is-no-longer-effective-or-desirable-institutions-need-to-rethink-their-value-proposition-of-transnational-higher-education" data-pm-slice="1 1 []">Australian international higher education is facing a crisis as visa approval rates plummeted in 2024, affecting institutions and potential students. The higher education sector faces the gloomy uncertainty of a cap to be introduced on international student enrollments. The Australian government has urged higher education institutions to set up more offshore delivery. However, the business-as-usual approach is no longer effective or desirable. Institutions need to rethink their value proposition of transnational higher education.